2005
DOI: 10.1111/j.1399-3011.2005.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic peptidomimetic strategies for autoimmune diseases: costimulation blockade*

Abstract: Cognate interactions between immune effector cells and antigen-presenting cells (APCs) govern immune responses. Specific signals occur between the T-cell receptor peptide and APCs and nonspecific signals between pairs of costimulatory molecules. Costimulation signals are required for full T-cell activation and are assumed to regulate T-cell responses as well as other aspects of the immune system. As new discoveries are made, it is becoming clear how important these costimulation interactions are for immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 123 publications
0
52
0
Order By: Relevance
“…However, if direct ligation of platelet CD154, not just FcR binding, is responsible for certain complications, this drawback will remain. Peptidomimetics can also provide a way to block CD40-CD154 interactions (49). However, peptide-binding affinities can frequently be modest, requiring large and potentially impractical quantities to effectively compete with CD154 for CD40 binding.…”
Section: Discussionmentioning
confidence: 99%
“…However, if direct ligation of platelet CD154, not just FcR binding, is responsible for certain complications, this drawback will remain. Peptidomimetics can also provide a way to block CD40-CD154 interactions (49). However, peptide-binding affinities can frequently be modest, requiring large and potentially impractical quantities to effectively compete with CD154 for CD40 binding.…”
Section: Discussionmentioning
confidence: 99%
“…Peptidomimetics are also water-soluble and are non-immunogenic. This allows them to be administered for longer periods of time [65]. It, therefore, seems possible to speculate that peptidomimetics may be useful in future therapies that need to modulate proteinprotein interactions, and in the case of sepsis, activate anti-apoptotic proteins, which may protect those cells from apoptosis normally lost during the course of the disease.…”
Section: Apoptotic Targets and Therapeutic Considerations Targeting Tmentioning
confidence: 99%
“…Previous data revealed that the peptidomimetic is water soluble and nonimmunogenic (64). In comparison with Smac, Smac mimetic could cross the cell membrane and bind efficiently to its target proteins (65).…”
Section: Targeting Livin By Blocking Protein Functionmentioning
confidence: 99%